2020
DOI: 10.1084/jem.20190971
|View full text |Cite
|
Sign up to set email alerts
|

Chloride intracellular channel 1 cooperates with potassium channel EAG2 to promote medulloblastoma growth

Abstract: Ion channels represent a large class of drug targets, but their role in brain cancer is underexplored. Here, we identify that chloride intracellular channel 1 (CLIC1) is overexpressed in human central nervous system malignancies, including medulloblastoma, a common pediatric brain cancer. While global knockout does not overtly affect mouse development, genetic deletion of CLIC1 suppresses medulloblastoma growth in xenograft and genetically engineered mouse models. Mechanistically, CLIC1 enriches to the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…Increased production of ROS is a hallmark of cell senescence, which also regulates the activation of CLICs. In recent years, the biological functions of CLICs in the pathological progression of diseases, such as CLIC4 regulation of pulmonary hypertension by activating Arf6 [25], CLIC2 inhibition of cardiac muscle ryanodine receptor [26], as well as CLIC1 and CLIC3 involvement in cancer development [27][28][29], have sparked considerable interests. Even though the role of CLICs in cancer has been extensively discussed, its role in age-related CVD has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased production of ROS is a hallmark of cell senescence, which also regulates the activation of CLICs. In recent years, the biological functions of CLICs in the pathological progression of diseases, such as CLIC4 regulation of pulmonary hypertension by activating Arf6 [25], CLIC2 inhibition of cardiac muscle ryanodine receptor [26], as well as CLIC1 and CLIC3 involvement in cancer development [27][28][29], have sparked considerable interests. Even though the role of CLICs in cancer has been extensively discussed, its role in age-related CVD has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that CLIC1 was upregulated in a variety of tumors and can be used as a poor marker, which involved with the regulation of angiogenesis, migration, invasion and apoptosis 14,25 . Francisco et al have revealed that overexpression of CLIC1 could cooperate with EAG2, leading to the dysregulation of cells volume homeostasis, RNA biosynthesis, and the activation of the p38 MAPK pathway, thus promoting cell proliferation and tumor growth in human medulloblastoma 26 . Moreover, CLIC1 was also affirmed to be a secreted protein, existed in extracellular vesicles comprising exosomes and microvesicles which released by glioblastoma multiforme (GBM) cells, and could regulate the properties of cancer stem cells (CSCs) and pro‐tumorigenic response in GBM progression 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-promoting role of CLIC1 has been reported in a variety of tumors [12,14,15]. Indirectly, miR-124 inhibits the proliferation, migration, and invasion of liver cancer cells by targeting CLIC1 [24];…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CLIC1 is upregulated in a variety of different cancers, such as oral squamous cell carcinoma [8], epithelial ovarian cancer [9], gastric cancer [10], gallbladder cancer [11], pancreatic cancer [12], and gliomas [13], and increased CLIC1 levels are associated with a poor prognosis in these patients. Moreover, knockout of CLIC1 inhibits medulloblastoma growth in xenograft and genetically engineered mouse models [14].…”
Section: Introductionmentioning
confidence: 99%